Biological generation of reactive alkaline species and their application in a sustainable bioprocess for the remediation of acid and metal contaminated wastewaters - Van Hille, Robert Paul (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2002)
This project focused on the development of an integrated biological system for the treatment of acidic and metal-laden effluents, based on the sustainable biological generation of reactive alkaline species. Initial studies concentrated on the binding and accumulation of heavy metals by biomass of the cyanobacteria, Spirulina sp. Metal binding was rapid, with saturation reached in 30 minutes, and followed an affinity series of Pb > Cu > Zn >>Fe. The binding capacity of the Spirulina for each of the metals was relatively low when compared to a range of other biosorbents. The toxicity thresholds of the algae was determined for copper and zinc. These were low (10umoles/g) and as such, the algae were not suitable for application in a treatment system in which they came into direct contact with the toxic metals. The algae were able to increase the pH of the surrounding medium. This occurred as a result of the accumulation of inorganic carbon, from bicarbonate, as a response to low concentrations of carbon dioxide in the medium. The resulting release of a hydroxide ion into solution led to the increase in pH. The increase in pH was shown to be due to a reduction in acidity, rather than an increase in alkalinity. The enzyme carbonic anhydrase was shown to be pivotal in this system. Attempts to determine the enzyme activity directly were unsuccessful, due to the inherent inaccuracy of the assay system. An indirect method of determining enzyme activity, by measuring changes in the carbonate species equilibrium, was developed. Under optimal conditions Spirulina was able to reduce the acidity by an amount equivalent to the addition of 3670umoles NaOH g·' h·'. Predictive modelling showed that this enhanced the potential of the medium to effect metal precipitation. For the algal system to be sustainable, a readily available source of bicarbonate was needed. This was achieved by the oxidation of organic carbon, under sulphidogenic conditions, by a bacterial consortium isolated from the anaerobic component of a facultative pond. The consortium was shown to consist of sulphate reducing (most likely Desulvovibrio and Desulfotomaculum)and acetogenic bacteria. Sulphate removal rates of 500mg 1·' day·' and 135mg 1·' day·' were achieved in a 21 agitated and 281 upflow reactor respectively. The bicarbonate generation rate in the 281 reactor was calculated as 4033umoles 1·' day·', which proved sufficient to act as a feed for the algal system. Sparging the anaerobic digester overflow with air and nitrogen resulted in a reduction in the aqueous sulphide concentration. Using nitrogen, a 70% recovery of sulphide, as H2S gas, was achieved in 60 minutes, while with air, this dropped to 40%, due to the oxidation of the aqueous sulphide. The stripping ofH2S resulted in an increase in pH. The H2S gas was used for the selective precipitation of copper and lead in the integrated system. The dynamics of metal precipitation was investigated. For simple reactions, between individual IV metal and base species, it was possible to generate an accurate predictive model and confirm the precipitating species using wavelength dispersive X-ray spectroscopy (WDS). In more complex systems, where precipitation of the artificial acid mine drainage was examined, the predictive modelling and WDS could not accurately describe the system. The addition of aqueous sulphide to copper and iron resulted in the formation of metastable, amorphous precipitates, which remained in suspension. Ageing of the copper precipitate resulted in the evolution of a stable crystalline structure (covellite) and the aggregation and settling of the precipitate. In the case of iron, the amorphous precipitate underwent oxidation before a stable iron sulphide could evolve and the settled precipitate was an iron oxide or oxyhydroxide. The artificial acid mine drainage was treated with sulphide, hydroxide, anaerobic digester overflow and algal overflow. The best metal removal was achieved with the sulphide and hydroxide, while the algal overflow outperformed the anaerobic digester overflow. The precipitate generated by the addition of sulphide was the most compact, followed by the algal overflow, the anaerobic digester overflow and the hydroxide. Efficient precipitation of all the heavy metals, except manganese, was achieved using the algal overflow at an acidity to alkalinity ratio of 1 :2. This ratio was selected for use in the pilot system. The Spirulina based pilot system was effectively used to treat an effluent from the Black Mountain base metal mine. The necessity to maintain the algae in suspension and avoid biomass washout were practical considerations which counted against this system. The replacement of the Spirulina by Oscillatoria, which adhered to a solid support, overcame these problems. The integrated biological system was able to effectively treat an artificial acid mine drainage for 90 days, reducing the concentration of all metals, except manganese, to below the acceptable environmental risk levels. The treatment of the final effluent in a second anaerobic digester reduced the manganese concentration to 4.5uM and proved that the sulphate reducing bacteria could be cultivated on enriched, partially treated acid mine drainage. The integrated biological treatment system performed well, effectively treating an effluent modelled closely on the quality of the water being discharged from the East Rand Basin. The cost of such a system would be considerably less than a "high tech" physico-chemical system. This, coupled with the potential long term sustainability of a biological system, would make it a potentially attractive option for the treatment of future acid mine drainage discharges.
Keywords: Uncatalogued